2017
DOI: 10.1159/000485451
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Signature of Two Long Non-Coding RNAs in Peripheral Blood Predicts Acute Renal Allograft Rejection

Abstract: Background/Aims: Acute rejection (AR) is a major complication post renal transplantation, with no widely-accepted non-invasive biomarker. This study aimed to explore the expression profiles of long non-coding RNAs (lncRNAs) in the peripheral blood (PB) of renal transplant recipients and their potential diagnostic values. Methods: The genome-wide lncRNA expression profiles were analyzed in 150 PB samples from pediatric and adult renal transplant (PRTx and ARTx) cohorts. The diagnostic performance of differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
(49 reference statements)
1
17
0
Order By: Relevance
“…However, here we analyzed four pre-selected lncRNAs, thus analyses of other lncRNAs in AR may yield additional associations and may potentially be important for prediction of (vascular injury after) AR. This is in line with two other studies that showed an association between lncRNAs and AR that suggested their value for diagnosis of AR in kidney transplantation [ 21 , 22 ]. Moreover, in a rat study, the lncRNA PRINS was shown to be significantly up-regulated in kidneys of rats with cold ischemia-elicited allograft rejection, compared with rats without rejection [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, here we analyzed four pre-selected lncRNAs, thus analyses of other lncRNAs in AR may yield additional associations and may potentially be important for prediction of (vascular injury after) AR. This is in line with two other studies that showed an association between lncRNAs and AR that suggested their value for diagnosis of AR in kidney transplantation [ 21 , 22 ]. Moreover, in a rat study, the lncRNA PRINS was shown to be significantly up-regulated in kidneys of rats with cold ischemia-elicited allograft rejection, compared with rats without rejection [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…Ge et al . showed that two LncRNAs, called AF264622 and AB209021, which were obtained in the peripheral blood cells, were increased in patients with acute kidney allograft rejection 10 . Another study indicated that urinary LncRNAs, called RP11-395P13.3-001 and RP11-354P17.15-001, were upregulated in patients with acute kidney allograft rejection 11 .…”
Section: Discussionmentioning
confidence: 99%
“…AF264622 and AB209021 are two lncRNAs upregulated in peripheral blood from pediatric and adult renal transplant patients with AR. Their high sensitivity and specificity to detect AR make them a promising alternative in the search for non-invasive biomarkers of AR in both pediatric and adult renal transplant recipients [28].…”
Section: Long Non-coding Rnasmentioning
confidence: 99%
“…Moreover, lncRNAs can interact with epigenetic regulators and transcription factors in a sequence-independent manner through non-coding transcription [5]. Multiple studies link lncRNA dysregulation and pathological disease states that affect the kidney, such as acute kidney injury (AKI), chronic kidney disease, nephropathies, and allograft rejection [27][28][29].…”
Section: Introductionmentioning
confidence: 99%